University Business Innovating - Quero-Gervilla, María José (My University, 2019)
Purpose – The aim of the present paper is to explore whether in the context of universities as complex services, it is possible to develop new business models rooted in Service Dominant Logic (SDL), where the constituent actors generate resources and co-create value for and within the system. In this context, the innovating perspective (Russo-Spena et al. 2017) can bring to universities the need for the development of institutions in universities (Vargo and Lusch, 2016) that bring out new co-creation formulas (such as co-patenting and co-ownership), which in turn facilitate “system equilibrium” (balanced centricity) in university and business contexts. Methodology– A conceptual approach is applied to develop and propose a framework for a deeper understanding of the “University Business Ecosystem” from the perspectives of SDL (Vargo and Lusch, 2016) and value co-creation (Russo-Spena and Mele, 2012; Quero and Ventura, 2015). Quantitative and qualitative case-study research was conducted using various methods of generating data, including personal interviews and a netnographic analysis of 95% of public universities in Spain.
Keywords: Innovating; Service Dominant Logic; University